2017
DOI: 10.1186/s12902-017-0169-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to and factors associated with self-care behaviours in type 2 diabetes patients in Ghana

Abstract: BackgroundPrevious research has failed to examine more than one self-care behaviour in type 2 diabetes patients in Ghana. The purpose of this study is to investigate adult Ghanaian type 2 diabetes patients’ adherence to four self-care activities: diet (general and specific), exercise, self-monitoring of blood glucose (SMBG) and foot care.MethodsConsenting type 2 diabetes patients attending diabetes outpatient clinic appointments at three hospitals in the Tamale Metropolis of Ghana completed a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
118
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(148 citation statements)
references
References 54 publications
21
118
7
2
Order By: Relevance
“…Contrary to Okolie et al () and Mogre et al (), in this study, there was no association between gender, educational attainment and DSM/adherence. This may be due to the fact that the authors made use of a different scale where different aspects of self‐management—blood glucose monitoring, foot care, diet adherence and adherence to exercise —were individually compared with the sociodemographic parameters, whereas in this study a sum scale encompassing the various aspects of self‐management was used.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to Okolie et al () and Mogre et al (), in this study, there was no association between gender, educational attainment and DSM/adherence. This may be due to the fact that the authors made use of a different scale where different aspects of self‐management—blood glucose monitoring, foot care, diet adherence and adherence to exercise —were individually compared with the sociodemographic parameters, whereas in this study a sum scale encompassing the various aspects of self‐management was used.…”
Section: Discussioncontrasting
confidence: 99%
“…Okolie et al () reported that individuals with primary school or no education adhered better than those with secondary and tertiary education. This is contrary to the report of Mogre et al (). Abubakari, Cousins, Thomas, Sharma, and Naderali () further documented the association between diabetes duration and self‐management although Huang, Zhao, Li, and Jiang () found the opposite among Chinese participants.…”
Section: Introductioncontrasting
confidence: 98%
See 1 more Smart Citation
“…We expected that this intermittent empagliflozin supplementation would encourage the participants to self‐manage their diet continuously, then appreciate their achievements with regard to HbA1c and body weight reduction and recognize this self‐efficacy (confidence in one's ability to execute a behaviour and manage one's life), and that this would further motivate their dietary self‐management. Therefore, although diet therapy can be frustrating and a burden, resulting in decreasing motivation with regard to self‐management, the participants' QoL was not decreased but increased compared with baseline in the setting of decreased dietary intake in the intermittent treatment group. Importantly, none of the participants in the intermittent group discontinued the study because of dissatisfaction or AEs.…”
Section: Discussionmentioning
confidence: 92%
“…Ten included studies evaluated foot care among diabetes patients from which two studies investigated foot care only (Shown in Table ). Six studies (Al‐Amer et al, ; Ashur et al, ; Assah et al, ; Bhandari & Kim, ; Mogre, Abanga, et al, ; Mosha & Rashidi, ) reported foot care adherence according to the mean number of days diabetes patients adhered to foot care recommendations; mean days ranged from 2.2–4.3 days in a week. Huang et al () reported a mean foot care practice score of 77.47% among Chinese persons with diabetes (higher scores indicate better self‐perceived overall foot care).…”
Section: Resultsmentioning
confidence: 99%